(untitled) (International journal of artificial intelligence, 2025)
The Progress in International Reading Literacy Study (PIRLS) provides valuable insights into students’ reading comprehension and cognitive skills. Its methodologies offer significant didactic opportunities for integrating literacy instruction across various subjects, promoting inquiry-based learning, metacognitive strategies, and interdisciplinary approaches. Incorporating PIRLS principles enhances reading engagement, critical thinking, and academic success. Additionally, technology, culturally responsive materials, and assessment-driven instruction further optimize literacy development. This paper explores the integration of PIRLS in education, emphasizing its role in fostering inclusive and effective teaching practices. Implementing PIRLS-based strategies ensures students acquire essential literacy skills for lifelong learning and real-world applications.